Pengaruh Penggunaan Yudane Tepung Lokal Terhadap Kualitas Roti Shokupan - Sholahuddin Al Ayyubi; Cucu Cahyana; Ari Fadiati (LPPM Universitas Negeri Jakarta, 2023)
This research aims to analyze the quality of shokupan bread using yudane with local ingredients including rice flour, glutinous rice flour, and mocaf flour. The research was conducted at the Pastry & Bakery Laboratory, Department of Culinary Education, Faculty of Engineering, Jakarta State University. The method used in this research was an experiment, analyzing the quality of shokupan bread with a 20% local yudane. The quality testing was performed by 5 trained panelists using a hedonic quality scale, including external factors such as volume, shape symmetry, uniformity of baking, and crust characteristics, as well as internal factors such as pores, crumb color, texture, aroma, taste, and chewing quality. The research results showed that among the external factors, the shokupan bread variant with mocaf-based yudane obtained the highest score in terms of volume with a value of 3.8. Meanwhile, in terms of crust color, the shokupan bread variant with glutinous rice flour-based yudane received the highest rating with a value of 3.8. On the aspect of shape symmetry, the shokupan bread variant with rice flour-based yudane obtained the highest score of 3.2. In terms of internal factors, the shokupan bread variant with glutinous rice flour-based yudane showed the highest ratings in terms of pores (3.4), crumb color (3.4), texture (3.4), taste (3.4), and chewing quality (4.0). However, the aspect of aroma received the highest rating in the shokupan bread variant with mocaf-based yudane with an average value of 3.2. In conclusion, based on the research results, shokupan bread made with glutinous rice flour-based yudane produced the best quality bread.